2017
DOI: 10.1016/j.drugalcdep.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

The impact of long-term moderate and heavy alcohol consumption on incident atherosclerosis among persons living with HIV

Abstract: Background Level of alcohol consumption is associated with differential risk of atherosclerosis, but little research has investigated this association among HIV+ persons. We evaluated the association between long-term alcohol use and incident atherosclerosis among HIV+ persons. Methods We utilized data from HIV+ participants of the Women’s Interagency HIV Study (n = 483) and the Multicenter AIDS Cohort Study (n = 305) without history of cardiovascular disease. Atherosclerosis was assessed two times by B-mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Our findings of moderate alcohol consumption in relation to decreased C-IMT measured at baseline confirm the results of some earlier studies [ 9 , 10 , 13 17 , 19 , 21 , 36 ] but not all [ 11 , 25 , 30 , 32 34 ]. Among the few studies [ 12 , 36 ] that have investigated the association between alcohol consumption and progression of atherosclerosis including both men and women, our study is one of the largest. Our findings of lower C-IMT progression in relation to moderate and high alcohol consumption, as compared to very low consumption, agree to some extent with those reported from an Italian study ( n = 780) [ 12 ] but disagree with those of an American study ( n = 788) [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of moderate alcohol consumption in relation to decreased C-IMT measured at baseline confirm the results of some earlier studies [ 9 , 10 , 13 17 , 19 , 21 , 36 ] but not all [ 11 , 25 , 30 , 32 34 ]. Among the few studies [ 12 , 36 ] that have investigated the association between alcohol consumption and progression of atherosclerosis including both men and women, our study is one of the largest. Our findings of lower C-IMT progression in relation to moderate and high alcohol consumption, as compared to very low consumption, agree to some extent with those reported from an Italian study ( n = 780) [ 12 ] but disagree with those of an American study ( n = 788) [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some of the studies have described the relationship between alcohol consumption and atherosclerosis as linear, with either increased [ 22 , 25 ] or decreased C-IMT [ 13 , 16 ] associated with a rise in alcohol consumption, whereas others report a J-shaped association, with a decrease of C-IMT with moderate alcohol consumption and an increase of C-IMT with high alcohol consumption [ 9 , 14 , 15 , 17 ]. Few studies, mainly performed in men [ 23 , 24 , 27 , 28 ], often with heavy or binge drinking habits [ 23 , 24 , 27 ], have investigated the relationship between alcohol consumption and progression of atherosclerosis, and results were discrepant [ 12 , 23 , 24 , 27 , 28 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding drinking habits, we did not find association between this social habit and the development of atherosclerosis. Recently, this relationship was found to be positive in patients with atherosclerosis and other cardiovascular diseases in other populations studied elsewhere (Kelso-Chichetto et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…A meta-analysis between 1999 and 2014 found only 13 eligible studies and estimated that heavy alcohol use was associated with 37% [95% CI 1.02–1.84] increased risk of cardiovascular disease compared to non-heavy use [98]. Recent longitudinal data from the Women’s Interagency HIV Study (WIHS) and the Multicenter AIDS Cohort Study (MACS) did not find an association of heavy alcohol use and incident atherosclerosis [99]. A prior cross-sectional study from MACS found an association between heavy alcohol use and the presence of coronary artery stenosis with no significant association for low/moderate drinking among PLWHA [96].…”
Section: Cvd and Hiv In Special Populationsmentioning
confidence: 99%